Qualitative Study of Midwives' Perceptions and Responses to the Implementation of Female Genital Mutilation (Circumcision) by Midwives in Aceh Post-Regulation - Mulyana, Eka; Nurjannah, Nurjannah; Zaman, Nasrul; Saputra, Irwan; Maidar, Maidar (PT Inovasi Pratama Internasional, 2025)
traditional and religious practice for girls in Aceh. While Indonesia has ratified international agreements banning Female Genital Mutilation/Cutting (FGM/C), implementation faces unique challenges in Aceh due to strong cultural and religious influences on healthcare practices. Objective: This study examined midwives' implementation of female circumcision following 2024 regulations, exploring practice challenges, conflicts between professional ethics and cultural values, and clinical implications. Methods: We conducted qualitative, phenomenological interviews with 18 midwives from four Aceh regions (Banda Aceh, Southwest Aceh, Central Aceh, and East Aceh), selected through snowball sampling, to capture diverse experiences. Results: Perceptions and responses to FGM regulations, along with value conflicts between legal requirements, professional ethics, and cultural/religious norms. Conclusion: The 2024 regulations have positioned midwives as key agents of change in eliminating FGM/C.However, effective implementation is hindered by information gaps, strong cultural resistance, and insufficient government support.